Lizards from suburban areas learn faster to stay safe. (28th February 2019) - Batabyal, Anuradha; Thaker, Maria
Abstract : Enhanced cognitive ability is beneficial in unpredictable and harsh environments, as it enables animals to respond with flexibility. For animals living in urbanized areas, local environments not only are altered but can rapidly change during their lifetime. Urban residents are therefore challenged with identifying novel dangers and safe refuges in dynamic environments. We demonstrate that the tropical agamid lizard Psammophilus dorsalis experiences dramatically different habitats not only across the rural to urban spatial scale but also over the short temporal scale of a few years in suburban areas. Differences in environmental stability are expected to affect rates of learning and reversal learning in resident lizards. In testing arenas, lizards from these populations were required to choose a designated 'safe' refuge instead of an 'unsafe' one after simulated predator attacks. The contingency for safety was switched during the reversal learning task. In general, P. dorsalis showed high rates of learning and reversal learning, but lizards from suburban areas were quicker to learn and unlearn the location of the safe refuge than those from rural areas. This demonstrates for the first time to our knowledge that suburban lizards have faster learning and reversal learning skills for a key survival-related behaviour, finding safety in unpredictable environments.